PROSPECTS FOR OIL AND GAS INDUSTRY DEVELOPMENT - Irina A. Senyugina; Yulia V. Starodubtseva (Вестник Северо-Кавказского федерального университета)
The national oil and gas industry in Russia is successfully operating, yet it has a number of issues that will soon require urgent action: high depreciation of equipment, low level of raw material processing, imperfect tax system and so on. Its future prosperity depends on how fast and comprehensively the industry can resolve the existing issues, also taking into account the global trends.